PENGARUH KINERJA LINGKUNGAN TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL PEMODERASI - AYU MARDIANA, INDAH; WURYANI, ENI (Jurnal Akuntansi AKUNESA, 2019)
This study aims to examine the effect of environmental performance on firm value with profitability as a moderating variable. The population of this study is a manufacturing company listed on the Indonesia Stock Exchange in 2014-2017. Obtained sample of 33 companies with 132 observations from purposive sampling technique. The results showed that environmental performance has a positive effect on firm value and profitability can moderated the relationship between environmental performance to firm value.